Investigation of the pathophysiological mechanism for altered calcium homeostasis in hyperthyroid cats. (23rd June 2013) - Williams, T. L.; Elliott, J.; Berry, J.; Syme, H. M.
<x xml:space="preserve">Abstract</x> Objective To investigate possible pathophysiological mechanisms (reduced plasma calcitriol concentrations and/or presence of concurrent or masked chronic kidney disease) for hypocalcaemiain hyperthyroid cats. Methods Prospective cohort study. Routine plasma biochemical parameters, plasma parathyroid hormone and calcitriol concentrations, ionized calcium concentrations, and venous pH, were measured at diagnosis and following treatment of hyperthyroidism. Linear regression analysis was used to determine predictors of ionized calcium concentration. Results Hyperthyroid cats (n=45) had lower ionized calcium concentrations than healthy geriatric cats (n=52), however, ionized calcium concentrations were higher in hyperthyroid cats with concurrent or masked chronic kidney disease than non‐azotaemic hyperthyroid cats. Plasma calcitriol concentrations were higher in hyperthyroid cats than control cats. Plasma total thyroxine concentration and venous pH were independent predictors of ionized calcium concentration. Plasma total thyroxine concentration was also a predictor of ionized calcium concentration after adjustment for plasma parathyroid hormone and calcitriol concentrations. Clinical Significance Hypocalcaemia in hyperthyroid cats is not associated with the presence of concurrent or masked chronic kidney disease or reduced plasma calcitriol concentrations. Increased thyroid hormone concentrations might influence ionized calcium concentrations through a mechanism, yet to be determined, that is independent of control by parathyroid hormone and calcitriol.